SONGKOK RECCA TO BONE; IDENTITAS LOKAL YANG MENASIONAL - Jumadi; Nurlela; Asmunandar; Khaeruddin; Andi Dewi Riang Tat; Bahri (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study of Songkok Recca to Bone is a study that tries to uncover the history of existence, the meaningful value of the songkok recca tersbut and the socioeconomic impact of recca songkok kerajiann for msayarakat in Paccing Village. This research as a study of local history that elevates local handicrafts as a cultural product that has economic value. The research method in this study is historical method with heuristic steps (data collection), criticism (verification), interpretation and historiography (writing). The use of the hat "Songkok Recca" is believed to have begun during the reign of the 31st Bone King named Andi Mappanyukki. The "Songkok Recca" hat used can show the wearer's social strata. This study aims to see the perception in the use of this hat is related to the social stratification of Bugis people in Bone Regency. The research was conducted in Awangpone Subdistrict, Bone Regency, South Sulawesi Province, using qualitative approach, with purposive sampling technique in determining informants. Data collection method using observation and interview, with the number of informants as many as ten people. Data analysis techniques in this research are qualitative data analysis techniques. The results showed that there is a shift in the use of the hat "Songkok Recca" today. Inistilah social stratification, the use of the hat "Songkok Recca" no longer shows the level of a person, but is now more described as a form of local wisdom bugis community in Bone Regency.